EFEKTIFITAS MODEL PEMBELAJARAN KOOPERATIF JIGSAW II DANTEAMS-GAMES-TOURNAMENTS (TGT) PADA MATERI BARISAN DAN DERET DITINJAU DARI TIPE KEPRIBADIAN SISWA SMK KELAS X DI KABUPATEN KLATEN - Mirati, Luthfiana; Riyadi, Riyadi; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objectives of this research were to find out on  the topic of Sequences and Series: (1) which had better learning achievement among cooperative learning Jigsaw II, cooperative learning TGT or a direct learning; (2) which had better learning achievement between melancholies students, phlegmatic students, sanguine students or choleric students; (3) at each personality types, which had better learning achievement among Jigsaw II, TGT or direct learning, and (4) at each learning models, which had better learning achievement between melancholies students, phlegmatic students, sanguine students or choleric students. This research was a quasi-experimental with 3×4 factorial design. The population was all students in tenth grade of vocational schools technology, health, and agriculture in Klaten Regency on Academic Years 2012/2013. Sampling was done by stratified cluster random sampling technique. The total of sample was 233 students. Statistical tests using the method Lilliefors test for normality, homogeniety of the Bartlett method, anava test with F test (Fisher) and post hoc test using the Scheffe’ method. The significance level was 0,05. Based on hypothesis test, it could  be concluded as follows: (1) TGT had better learning achievement than Jigsaw II and direct learning, Jigsaw II had better learning achievement than direct learning; (2) there were no any differences in the learning achievement in mathematics of the students with melancholies, phlegmatic, sanguine or choleric personality types; (3) in each personality types, the cooperative learning model TGT had better than cooperative learning Jigsaw II, and both result had better learning achievement in mathematics than the direct learning model; (4) in each learning model, the students with melancholies, phlegmatic, sanguine or choleric personality types have the same learning achievement.Keywords: Melancholies, Choleric, Phlegmatic, Sanguine, TGT, Jigsaw II and Direct learning.